Pengaruh Citra Merek Dan Harga Terhadap Keputusan Pembelian Di Kota Ambon - Joshua David Kiswanto; Harold Hursepuny; Deflin Tresye Nanulaitta; Simson Melmambessy (P3M Politeknik Negeri Ambon, 2023)
Factors that influence purchasing decisions do not only come from consumers, but also influenced by the marketing strategy of a company or business group. Brand image and price are an inseparable part of the factors behind the purchase decision at Ambon. This study aims to examine and analyze the effect of brand image and price on purchasing decisions at Passo Electronic Store. The analytical method used is multiple linear regression analysis using SPSS software version 21.0. The results of the research, hypothesis one produces a tcount value of 2.030 with a significant value of 0.047 < 0.05, hypothesis two produces a tcount value of 4.790 with a significant value of 0.000 < 0.05 and hypothesis three produces an Fcount value of 25.160 with a significant value of 0.000 < 0.05. Based on the results of the study, it can be said that brand image has a positive effect on purchase decisions at Passo Electronic Store. Price has a positive effect on purchase decisions at Passo Electronic Store. Brand image and price together have a positive effect on purchasing decisions at the Passo Electronic Store. Brand image and price have an influence on purchse decisions by 47.2% while the remaining 52.8% is influenced by other variables. Based on the analysis and discussion, research can submit sugestion: Passo Electronic Store must be able to maintain the adventages it has, should increase promotion or introduction about their product.Keywords: Brand Image, Price, Purchase Decision